2014
DOI: 10.5001/omj.2014.16
|View full text |Cite
|
Sign up to set email alerts
|

IQ Scores of Children with Moderate Asthma: A Comparison with Healthy Children

Abstract: Although asthma is a chronic disease and causes many respiratory problems, it has no negative impact on IQ.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 16 publications
3
15
0
Order By: Relevance
“…Our data revealed that allergic rhinitis, asthma, atopic dermatitis, and urticaria were not associated with children’s cognitive profiles. While allergic rhinitis is a chronic disease that effects quality of life, we identified no negative effects on IQ 26 . Although asthma is a chronic disease and causes many respiratory problems, it also has no negative impact on IQ 14 .…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…Our data revealed that allergic rhinitis, asthma, atopic dermatitis, and urticaria were not associated with children’s cognitive profiles. While allergic rhinitis is a chronic disease that effects quality of life, we identified no negative effects on IQ 26 . Although asthma is a chronic disease and causes many respiratory problems, it also has no negative impact on IQ 14 .…”
Section: Discussionmentioning
confidence: 64%
“…While allergic rhinitis is a chronic disease that effects quality of life, we identified no negative effects on IQ 26 . Although asthma is a chronic disease and causes many respiratory problems, it also has no negative impact on IQ 14 . Nevertheless, certain neurocognitive symptoms are increased in children with moderate-to-severe atopic dermatitis, compared to healthy controls 22 .…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…Most of the studies 141516 on academic performance of children with asthma have been in developed countries and despite the high prevalence of asthma among Nigerian schoolchildren,1718 only a few studies have investigated the relationship between IQ score and academic performance of children with asthma compared with those without. Ghaffari et al 8. in a comparative study of the overall IQ scores of asthmatics and healthy children found that there were no significant differences in the overall scores and in the scores of males and females.…”
Section: Introductionmentioning
confidence: 95%
“…Intelligence, measured as the intelligence quotient (IQ), is one of the important prognostic variables in the academic performance of a child,7 and many factors including chronic diseases may impact upon it 89. IQ scores, as has been suggested, may be an appropriate guide in the proper placement of schoolchildren at the beginning of their education 10.…”
Section: Introductionmentioning
confidence: 99%